SIFAT FISIK MEKANIK PAPAN PARTIKEL TANPA PEREKAT DARI TANDAN KOSONG KELAPA SAWIT (Elaeis Guineensis acq) - Cahyana, Budi Tri (Jurnal Riset Industri Hasil Hutan, 2014)
This research aimed to get the physical and mechanical properties of non adhesive-particle board from oil palm empty fruit bunches. The oil palm empty fruit bunches were degradated to fibre and boiled in boiling water during 60 minute then dried in Â± 2 weeks. The dried raw material was chopped to be fibre in 5 mesh, 10 mesh, and 16 mesh. It were complied into a mold and then hot pressed in 35 kgf/cm2 pressure during 10 minute with 3 of temperature variety, 160Â°C, 180Â°C and 200Â°C. The result showed that the average of particle board water content was 7,11 -Â  9,85 % and the density was 0,63 â 0,76 gr/cm3. The highest thickness swelling was 22,59 % in 10 mesh and 160 0C (a2b1) temperature of oil palm empty fruit bunches. The modulus of rupture was 211,67 kg/cm2Â  in 10 mesh and 180 0C (a2b2) temperature. The modulus of elasticity was 490,85 kg/cm2 in 10 mesh and 160 0C (a2b1) temperature. The tensile strength was 7,49 kg/cm2 in 5 mesh and 200 0C (a1b3) temperature. The average of physical and mechanical properties such as water content, density, modulus of rupture, tensile strength were fulfill the SNI requirement, while the average of thickness swelling and modulus of elasticity were not fulfill the SNI requirement.Keywords: oil palm empty fruit bunches, particle board